Digital filing and file control system (DFFCS) - Teh, Suet Khim (Universiti Malaysia Sarawak, UNIMAS, 2005)
This report is written to present the Digital Filing and File Control System (DFFCS). DFFCS is developed to replace conventional files management system and also to solve the problems that facing by current digital filing systems. Before proceeding to realization the system many researches and studies have been made. The purpose of the study is to have a better understand in the files management and the files control issues. This is because the files management and control issues have become more common and critical nowadays. DFFCS is developed for the intermediate office to store their company documents and employees’ personnel details. DFFCS has presented to be effective procedures for solving the files management and files control problems. The files control is performed by locking and unlocking the currently opened file in the database. The files in the database are arranged methodically according to alphabetical order for easier and convenience files searching and files retrieving.